2021
DOI: 10.18203/2349-3291.ijcp20212886
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical profile of children with severe acute malnutrition: an experience from nutritional rehabilitation centre in South Kashmir

Abstract: Background: Malnutrition is significant contributor of childhood morbidity and mortality in developing countries. More than 1/3rd of world’s severely malnourished children live in India. The aim was to evaluate the clinical-epidemiological profile and co-morbidities of SAM (severe acute malnutrition) children and to recognize socio-demographic risk factors of SAM children.Methods: It was a prospective hospital based case study. The prospective hospital based study was conducted from September 2018 to February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
4
2
0
Order By: Relevance
“…Females constituted the majority of study population as observed by other researchers [4,5]. This reflects differential care for baby of different gender in our study.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Females constituted the majority of study population as observed by other researchers [4,5]. This reflects differential care for baby of different gender in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Maximum number of children was in the age group of 6-12 month followed by those in the age group of 12-24 months. This has been observed in many other studies [5,6] and may be attributed to improper introduction of complementary feeds.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations